Evaluation of the efficiency of functioning of the nature reserve fund in the Pripet river basin in the Volyn region - Nekos, Alla; Boiaryn , Mariia; Karpyuk , Zoya; Kotsun , Larisa; Andreyeva, Valentina; Lugowska, Maria (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. Considerable attention of scientists at the current stage of development of society is given to the theory of formation and assessment of the state of the nature reserve network and its ability to ensure biodiversity. The upper part of the Pripet River basin in the Volyn region is marked by various nature-reserved objects that belong to the pan-European, national and regional eco-networks. The objective of the work is the assessment and territorial distribution of NRF within the Pripet River basin in Volyn. Methods. The research used a complex and systematic approach, as well as mathematical, cartographic and comparative descriptive methods. Results. The river basin contains 314 objects of the nature reserve fund (NRF) with a total area of 164,735.7 hectares. The actual area is 149,186.4 hectares as a number of objects that are included in the total area of the nature reserve fund are actually located within the boundaries of other NRF objects, much larger in area. There are more than 40 such objects in the Pripet river basin. Such objects located within several river basins are also found within the basins of the main tributaries of the Pripet – the Vyzhivka, the Turia, the Tsyr, the Stokhid, the Styr rivers. In the upper Pripet River basin, there is an uneven distribution of protected areas across the territory, which indicates the need to increase their size in the Styr, Turia, Vyzhivka, and Korostyanka river basins to achieve an optimal ratio of areas and conserve species biodiversity based on a basin approach. The results of the calculation of the insularity index of the NRF of the Volyn region and of the degree of protection within the river basins are presented. The effectiveness of the nature reserve fund of the Pripet River basin was assessed, where the actual area of the protected area is 149,186.4 ha, the density of objects is 2.14 per 100 km2, the degree of protection (Spro) is 10.17%, and the insularity index (I) is 0.32. Twelve species of flora included in the International Red Lists were identified (Daphne cneorum L., Cypripedium calceolus L., Aldrovanda vesiculosa L., Salvinia natans (L.) All., Jurinea cyanoides (L.) Rchb., Tragopogon ucrainicus Artemczuk., Silene lithuanica Zapal., Liparis loeselii (L.) Rich., Pulsatilla patens (L.) Mill., Saxifraga hirculus L., Galanthus nivalis L., Crataegus ucrainica Pojark.), the areas of distribution of which are protected areas located in the Pripet River basin. Conclusions. Prospectively, a successful expansion of the NRF area of the basin will make it possible to develop a national and pan-European eco-network, as well as to expand the area of wetlands of international importance.